Progress in circulating tumor cell capture and analysis: implications for cancer management. (April 2012) - Balic, Marija; Lin, Henry; Williams, Anthony; Datar, Ram H; Cote, Richard J
The hematogenous dissemination of cancer and development of distant metastases is the cause of nearly all cancer deaths. Detection of circulating tumor cells (CTCs) as a surrogate biomarker of metastases has gained increasing interest. There is accumulating evidence on development of novel technologies for CTC detection, their prognostic relevance and their use in therapeutic response monitoring. Many clinical trials in the early and metastatic cancer setting, particularly in breast cancer, are including CTCs in their translational research programs and as secondary end points. We summarize the progress of detection methods in the context of their clinical importance and speculate on the possibilities of wider implementation of CTCs as a diagnostic oncology tool, the likelihood that CTCs will be used as a useful biomarker, especially to monitor therapeutic response, and what may be expected from the future improvements in technologies.